Characterization of the Berry Quality Traits and Metabolites of ‘Beimei’ Interspecific Hybrid Wine Grapes during Berry Development and Winemaking - Yangfu Kuang; Chong Ren; Yi Wang; Gathunga Elias Kirabi; Yongjian Wang; Lijun Wang; Peige Fan; Zhenchang Liang (Horticulturae, 2022)
The development of grape varieties with cold resistance can be an advantage for the wine industry. ‘Beimei’, an interspecific hybrid wine grape variety with cold resistance and pleasant rose aroma, is now extensively cultivated in China. In the present study, the berry quality traits and metabolites of ‘Beimei’ and other “Bei” varieties were characterized. The sugar (234 g/L–391 g/L) and acid (6.2–8.3 g/L) contents of ‘Beimei’ and four additional “Bei” varieties, i.e., ‘Beihong’, ‘Beixi’, ‘Beixin’, and ‘Xinbeichun’ berries were smilar to that of traditional Vitis vinifera varieties. ‘Beimei’ grapes has the highest volatile compounds composition, especially the content of rose aroma compounds (2-phenyl-ethyl alcohol and neryl alcohol), which was significantly higher than that of the other “Bei” wine grape varieties. After fermentation, ‘Beimei’ wines showed improved quality, with a high resveratrol content (18 mg/L) compared to traditional Eurasian wines. In addition, the high content of main rose aroma compounds (acetic acid 2-phenylethyl acetate, phenylethyl alcohol, neryl alcohol and beta-damascenone) contribute to a pleasant rose aroma in ‘Beimei’ wines. In summary, these results indicate that ‘Beimei’ grapes could be used as a winemaking grape variety considering global climate changes.